2004
DOI: 10.1152/ajpgi.00314.2003
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides induced increases in Fas ligand expression by Kupffer cells via mechanisms dependent on reactive oxygen species

Abstract: Fas-Fas ligand (FasL)-dependent pathways exert a suppressive effect on inflammatory responses in immune-privileged organs. FasL expression in hepatic Kupffer cells (KC) has been implicated in hepatic immunoregulation. In this study, modulation of FasL expression of KC by endogenous gut-derived bacterial LPS and the role of reactive oxygen species (ROS) as potential mediators of FasL expression in KC were investigated. LPS stimulation of KC resulted in upstream ROS generation and, subsequently, increased FasL e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 38 publications
0
43
0
1
Order By: Relevance
“…They have been suggested to play an important role in clearing pathogens derived from the gut (500). They are also involved in the regulation of gene expression, particularly the expression of the CD95 ligand (890) and NFB-dependent production of TNF-␣ (753). Finally, they have been suggested to be essential mediators in antigen presentation by Kupffer cells (568).…”
Section: Livermentioning
confidence: 99%
“…They have been suggested to play an important role in clearing pathogens derived from the gut (500). They are also involved in the regulation of gene expression, particularly the expression of the CD95 ligand (890) and NFB-dependent production of TNF-␣ (753). Finally, they have been suggested to be essential mediators in antigen presentation by Kupffer cells (568).…”
Section: Livermentioning
confidence: 99%
“…In the extrinsic pathway of apoptosis, ROS are generated by Fas ligand as an upstream event for Fas activation. In turn, ROS are required for Fas phosphorylation at the tyrosine residue, which is a signal for subsequent recruitment of Fas-associated protein with death domain and caspase 8 and for apoptosis induction (72,216,257,305). In addition, ROS are required for the ubiquitination and subsequent degradation of the FLICE inhibitory protein to further enhance Fas activation (322).…”
Section: Fig 2 Major Sources Of Ros Inside a Cancer Cellmentioning
confidence: 99%
“…It has been reported that the administration of TA activates NF-B followed by the generation of ROS in the liver (Lu et al, 1999), and it was also reported that LPS treatment increases the generation of ROS in Kupffer cells (Uchikura et al, 2004) and the NF-B binding activity in hepatocytes (Freedman et al, 1992). Reactive oxygen species contribute to the pathogenesis of a variety of liver diseases, such as acetaminophen overdose, hemochromatosis, alcoholic liver injury, toxin exposure, and viral hepatitis (Slater, 1984).…”
Section: Luminescence-based Analysis Of Nf-b Activation 449mentioning
confidence: 99%
“…In the LPS/ GalN-induced fulminant hepatitis model, Man-or Suc-catalase also effectively inhibited NF-B activation and liver injury. Because LPS is mainly recognized by the toll-like receptor 4 expressed on Kupffer cells (Su et al, 2000) and subsequently produce ROS (Uchikura et al, 2004) and inflammatory cytokines (Su et al, 2000), the delivery of catalase to the nonparenchymal cells is efficient. The cause of TAor LPS/GalN-induced death is reported to be ROS-mediated liver dysfunction (Okuyama et al, 2003).…”
Section: Downloaded Frommentioning
confidence: 99%